2002
DOI: 10.1080/003655202760230973
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Adult Coeliac Disease

Abstract: There was an inverse association between adult coeliac disease and cigarette smoking which was accounted for by middle-aged coeliacs having never smoked. These results are consistent with an age-dependent interaction between cigarette smoking and the other environmental factors implicated in coeliac disease, including gluten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 20 publications
1
30
2
Order By: Relevance
“…Still, it seems likely that sperm count and sperm volume and fertility are affected negatively by smoking (35). Most studies have suggested an inverse relationship between smoking and CD (36,37), but not all (38,39). If patients with CD are less often smokers, this possibility may have overestimated fertility in men with CD in our study.…”
Section: Strengths and Limitationscontrasting
confidence: 47%
“…Still, it seems likely that sperm count and sperm volume and fertility are affected negatively by smoking (35). Most studies have suggested an inverse relationship between smoking and CD (36,37), but not all (38,39). If patients with CD are less often smokers, this possibility may have overestimated fertility in men with CD in our study.…”
Section: Strengths and Limitationscontrasting
confidence: 47%
“…Adults with treated celiac disease are reported to be less likely to have a diagnosis of hypertension (OR: 0.68 [95% CI: 0.60-0.76]) and have a lower reported anti hypertensive medication use in comparison with age-and sex-matched general population controls [55]. Celiac disease appears to be associated with nonsmoking, although it is unclear whether or not this is a causal association [56][57][58]. However, smoking was more common in women with diagnosed celiac disease than those without celiac disease using data combined from national birth registers and the Swedish In-Patient Registry [59].…”
Section: Vascular Diseasementioning
confidence: 86%
“…50,51 A similar finding was reported for patients with CD alone, suggesting a protective role for smoking in CD similar to that seen in ulcerative colitis. [52][53][54] Whether the immunomodulation induced by smoking would have a protective effect on DH is unclear. Additional studies are necessary to determine if nicotine treatment may be a management option for these conditions.…”
Section: Pathogenesismentioning
confidence: 99%